The Influence of Macroeconomic Factors on Murabahah Financing Performance at Bank Syariah Indonesia - Ritonga, Khoirunnida; Imsar; Bi Rahmani, Nur Ahmadi (Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
Purpose: This study aims to examine the impact of macroeconomic variables—namely inflation, the BI rate, and the exchange rate—on murabahah financing at Bank Syariah Indonesia (BSI), both in the short and long term. Method: Employing the Vector Error Correction Model (VECM), the study analyzes time-series data to assess long-run equilibrium and short-term dynamics. Results: The findings reveal that in the long term, inflation and the BI rate negatively affect murabahah financing, while the exchange rate exerts a positive influence. In contrast, none of the variables show significant short-term effects. The Granger causality test identifies bidirectional relationships between the BI rate and both financing and inflation. Variance Decomposition shows that while financing is initially self-driven, over time inflation emerges as the most influential factor, accounting for 16.74% of variation in murabahah financing. Implication: These results suggest that Bank Syariah Indonesia should develop adaptive financing strategies in response to macroeconomic fluctuations, particularly inflation. Originality: This study contributes to Islamic finance literature by applying a dynamic econometric framework (VECM) to murabahah financing, and by offering empirical evidence from the post-merger period of Indonesia's largest Islamic bank.